If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + 6 + -1y = -5y + -4 Reorder the terms: 6 + -5y + -1y = -5y + -4 Combine like terms: -5y + -1y = -6y 6 + -6y = -5y + -4 Reorder the terms: 6 + -6y = -4 + -5y Solving 6 + -6y = -4 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. 6 + -6y + 5y = -4 + -5y + 5y Combine like terms: -6y + 5y = -1y 6 + -1y = -4 + -5y + 5y Combine like terms: -5y + 5y = 0 6 + -1y = -4 + 0 6 + -1y = -4 Add '-6' to each side of the equation. 6 + -6 + -1y = -4 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = -4 + -6 -1y = -4 + -6 Combine like terms: -4 + -6 = -10 -1y = -10 Divide each side by '-1'. y = 10 Simplifying y = 10
| 3+9c=10c | | 4x+30=x-15 | | 3+6f=5f | | x^2+81x+81=0 | | 5b-10=10b | | -7j+10=-10-9j | | 2x+6x=-85+5 | | 2g=-16 | | -g=10g | | -10+6u=4u | | n+19=3 | | -1-3x=9x-13 | | -w+3-10w=4-10w | | -6q=-4q-10 | | 4X^1=50 | | -5s=-8s+9 | | .4x-y+6=0 | | 3n-8/2*6=6 | | 4m-8=3m | | 6+10z=-10+6z | | 4z=6z+8 | | 2j=j+9 | | X^2-6x-96=-130 | | -3f+10=-10+7f | | -3f+10=-10 | | -5b-6=-111 | | 7m=8+6m | | 92+87+88+x=270 | | -22+3=m-5 | | -2n=8+2n | | x^2+42x+360=0 | | 6r-6=3r |